2005
DOI: 10.1097/01.mph.0000165134.38120.87
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Adolescent Idiopathic Scoliosis Using Thoracic Pedicle Screw Fixation Versus Hook Constructs

Abstract: This retrospective study was undertaken to determine the effectiveness and cost of thoracic pedicle screws versus laminar and pedicle hooks in patients undergoing surgical correction of adolescent idiopathic scoliosis (AIS). Immediate preoperative and 6-week postoperative radiographs were examined in 25 consecutive cases of children with AIS who were divided into two groups, those with thoracic pedicle screw constructs and those with thoracic hook constructs. Endpoints collected included radiographic measures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(35 citation statements)
references
References 21 publications
2
28
0
5
Order By: Relevance
“…The radiographic measurements in this study are comparable to those previously reported (Table 6) [12][13][14][15][16][17]. Major curve correction in the coronal plane was 73 % in the screw group and 56.9 % in the hook group.…”
Section: Discussionsupporting
confidence: 89%
“…The radiographic measurements in this study are comparable to those previously reported (Table 6) [12][13][14][15][16][17]. Major curve correction in the coronal plane was 73 % in the screw group and 56.9 % in the hook group.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, there are those who report similar major curve correction with similar loss of correction over time, similar fusion lengths, and similar SRS scores, with lower implant costs. 5,44,45 This similarity has been established especially when sublaminar wires are added in the hybrid construct. 45 These have been reported to be at least as safe and effective as other instrumentations.…”
Section: Discussionmentioning
confidence: 94%
“…Several authors have developed mathematical expressions in order to measure the morphology of scoliotic spines in three dimensions as well as the rotation of vertebrae [1][2][3]. Since then, correction of scoliosis deformity in frontal, sagittal and axial planes has been widely studied [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%